Identifying Toxic Impacts of Metals Potentially Released during Deep-Sea Mining—A Synthesis of the Challenges to Quantifying Risk - Hauton, Chris; Brown, Alastair; Thatje, Sven; Mestre, Nélia C.; Bebianno, Maria J.; Martins, Inês; Bettencourt, Raul; Canals, Miquel; Sanchez-Vidal, Anna; Shillito, Bruce; Ravaux, Juliette; Zbinden, Magali; et al. (Frontiers in Marine Science, 2017)
In January 2017, the International Seabed Authority released a discussion paper on the development of Environmental Regulations for deep-sea mining within the Area Beyond National Jurisdiction (the ‘Area’). With the release of this paper, the prospect for commercial mining in the Area within the next decade has become very real. Moreover, within nations’ Exclusive Economic Zones, the exploitation of deep-sea mineral ore resources could take place on very much shorter time scales and, indeed, may have already started. However, potentially toxic metal mixtures may be released at sea during different stages of the mining process and in different physical phases (dissolved or particulate). As toxicants, metals can disrupt organism physiology and performance, and therefore may impact whole populations, leading to ecosystem scale effects. A challenge to the prediction of toxicity is that deep-sea ore deposits include complex mixtures of minerals, including potentially toxic metals such as copper, cadmium, zinc, and lead, as well as rare earth elements. Whereas the individual toxicity of some of these dissolved metals has been established in laboratory studies, the complex and variable mineral composition of seabed resources makes the a priori prediction of the toxic risk of deep-sea mining extremely challenging. Furthermore, although extensive data quantify the toxicity of metals in solution in shallow-water organisms, these may not be representative of the toxicity in deep-sea organisms, which may differ biochemically and physiologically and which will experience those toxicants under conditions of low temperature, high hydrostatic pressure, and potentially altered pH. In this synthesis, we present a summation of recent advances in our understanding of the potential toxic impacts of metal exposure to deep-sea meio- to megafauna at low temperature and high pressure, and consider the limitation of deriving lethal limits based on the paradigm of exposure to single metals in solution. We consider the potential for long-term and far-field impacts to key benthic invertebrates, including the very real prospect of sub-lethal impacts and behavioural perturbation of exposed species. In conclusion, we advocate the adoption of an existing practical framework for characterising bulk resource toxicity in advance of exploitation.